THE ATTRACTION AND SELECTION OF ACCOUNTING TEACHERS. - Weimer, Arthur M.; Miller, Hermann C. (The Accounting Review, 1956)
Abstract This article focuses on attraction and selection of accounting teachers. The need of selection of accounting teachers is for a greater number of fine scholars to the collegiate schools of business or to business courses offered in liberal arts colleges. Secondly, having attracted fine scholars to the study of commerce, industry, and finance, it is equally important that they should not be alienated from accounting because of an early and intensive exposure to record keeping. The third important thing is to hold before the promising student the incentives, the variety of opportunities, the fascinating life which a career in accounting offers. Some of the criteria's for selection of accounting teachers are, good physical appearance, neatness in dress, professional bearing and attitude, and a good voice and speaking ability, sound underlying education having sufficient breadth and depth to provide a cultural background, technical proficiency through study, research, and practice and cheerful and enthusiastic disposition with an interest in people.